Effect of Modulated Electromyostimulation on the Motor System of Elderly Neurological Patients. Pilot Study of Russian Currents Also Known as Kotz Currents - Amirova, Liubov; Avdeeva, Maria; Shishkin, Nikita; Gudkova, Anna; Guekht, Alla; Tomilovskaya, Elena (Frontiers in Physiology, 2022)
In this brief report, we present preliminary findings from a study of the use of electromyostimulation (EMS) in neurological patients. Assuming the approach to be sufficiently effective, we decided to investigate the motor system of elderly neurological patients before and after a course of Russian currents EMS, which were developed for Soviet athletes and cosmonauts. To this point, 19 patients - EMS (n=11) and control (n=8) - have successfully completed the study. The study included patients aged 60-90 years with confirmed walking and balance disorders with a history of chronic cerebral ischemia. Patients in the experimental group underwent a course of modulated EMS of the hip and shin muscles from 3 to 9 procedures. Preliminary results of the study showed good patient acceptance of EMS. After the course, the EMS group showed a significant improvement from baseline in the Tinetti Test (+1.4 points, p=0.0045), Rivermead Mobility Index (+0.5 points, p=0.0022), and Timed Up and Go Test (-1.2 s, p=0.0053). There was also a significant improvement in balance quality of 8.6% (p=0.04). Shin muscle strength, although trending positively, did not change significantly. There was also no change in hip and shin muscles’ tone. No significant changes were observed in the control group in the same tests. It can be concluded that stimulation of the hip and shin muscles with Russian (Kotz) currents has a positive effect on the motor system of elderly neurological patients. Significant effects with a course of short duration indicate that this EMS regimen is promising.